Representation of Disability Achievements in Television Talk Show Programs - Setyowati, Retno Manuhoro; Setya Watie, Errika Dwi; Saptiyono, Ami (Universitas Semarang, 2020)
This study looks at how the disability presented in television talk shows program. It s important because the diffables in the media are often presented biased, causing misunderstandings. This can have an impact on the fulfillment of their rights by the government and also their social position. The use of representation theory to explain the process of media representation and interpret audience concepts using language. The analysis of research uses the Saussure semiotic method, because representation is closely related to the appearance of images, and other components, which are interrelated between markers and marked ones. The results showed that the media still placed disability as an object of inspiration, an object of pity should get a lot of appreciation in sports matches because of physical limitations. The media quickly found momentum to 'sell' disability stories that inspire. Achievement of disabilities is always related to money, not based on their rights.